Stimulation of Adenosine A2B Receptor Inhibits Endothelin-1-Induced Cardiac Fibroblast Proliferation and α-Smooth Muscle Actin Synthesis Through the cAMP/Epac/PI3K/Akt-Signaling Pathway - Phosri, Sarawuth; Arieyawong, Ajaree; Bunrukchai, Kwanchai; Parichatikanond, Warisara; Nishimura, Akiyuki; Nishida, Motohiro; Mangmool, Supachoke (Frontiers in Pharmacology, 2017)
Background and Purpose: Cardiac fibrosis is characterized by an increase in fibroblast proliferation, overproduction of extracellular matrix proteins, and the formation of myofibroblast that express α-smooth muscle actin (α-SMA). Endothelin-1 (ET-1) is involved in the pathogenesis of cardiac fibrosis. Overstimulation of endothelin receptors induced cell proliferation, collagen synthesis, and α-SMA expression in cardiac fibroblasts. Although adenosine was shown to have cardioprotective effects, the molecular mechanisms by which adenosine A2 receptor inhibit ET-1-induced fibroblast proliferation and α-SMA expression in cardiac fibroblasts are not clearly identified. Experimental Approach: This study aimed at evaluating the mechanisms of cardioprotective effects of adenosine receptor agonist in rat cardiac fibroblast by measurement of cell proliferation, and mRNA and protein levels of α-SMA. Key results: Stimulation of adenosine subtype 2B (A2B) receptor resulted in the inhibition of ET-1-induced fibroblast proliferation, and a reduction of ET-1-induced α-SMA expression that is dependent on cAMP/Epac/PI3K/Akt signaling pathways in cardiac fibroblasts. The data in this study confirm a critical role for Epac signaling on A2B receptor-mediated inhibition of ET-1-induced cardiac fibrosis via PI3K and Akt activation. Conclusion and Implications: This is the first work reporting a novel signaling pathway for the inhibition of ET-1-induced cardiac fibrosis mediated through the A2B receptor. Thus, A2B receptor agonists represent a promising perspective as therapeutic targets for the prevention of cardiac fibrosis.